A NARRATIVE LITERATURE REVIEW ON CHALLENGES FACED BY ENGLISH TEACHERS TO IMPLEMENT TECHNOLOGY-BASED PEDAGOGY IN ENGLISH AS A FOREIGN LANGUAGE (EFL) CLASSROOMS AROUND THE GLOBE - Shagufta Khurram; Zulfiquar Ali Chachar; Sayed Tanweer Ahmed (International Journal of Contemporary Issues in Social Sciences, 2024)
This review article investigates the literature available on the challenges encountered by English teachers in using technology-based pedagogy in English as a Foreign Language (EFL) classrooms worldwide. Journal research articles were included in the review. The review was carried out through a comprehensive analysis of the literature that was published between 2015 and 2022. The focus of the article is to review the difficulties faced by English as a Foreign Language (EFL) teachers who want to implement technology-based pedagogy in their classrooms around the world. To identify common barriers, the review integrates data from Google Scholar and Science Direct databases. These include challenges with technological availability, teacher training, intolerance to shift, cultural factors, ethnic multilingual considerations, instructional configuration, evaluation, and feedback collectively contributing to these challenges. Collaboration between educational organizations, decision-makers, and programs for teacher preparation is essential to overcoming these challenges. A further area of focus for continuing research is the creation of context-specific solutions for these problems. The review focuses on the necessity of targeted measures to address these problems and increase the effectiveness of technology integration in EFL instruction. It is strongly recommended to conduct more research in the future to identify solutions to the challenges English teachers confront when implementing cutting-edge teaching techniques and technology in EFL classrooms.